CONVERSION OF CO2 TO HYDROCARBON SYNFUEL BY UTILIZING NUCLEAR HYDROGEN COGENERATION - Djati H Salimy (Scientific Contributions Oil and Gas, 2018)
A study of the utilization of hydrogen cogeneration with nuclear energy as a technology for the conversion of CO2 into synthetic liquid hydrocarbon fuels has been carried out. The aim of the study is to understand the conversion of CO2 and H2 into synthetic fuels, as well as the role of nuclear hydrogen cogeneration for the production of hydrogen and as a source of process heat energy. The method used is literature study based on the results of existing research. Conventionally, synthetic fuel production from coal is produced through coal gasification process, followed by reacting synthesis gas (mixture of CO and H2) in FT reactor to synthesis fuel. In this study, we studied the production of synthetic fuels with CO2 and H2 raw materials. CO2 comes from emissions of coal-fired plants, whereas H2 is produced by nuclear hydrogen cogeneration systems. The results show that compared to conventional processes, CO2 and H2-based processes supported by coal cogeneration systems provide significant advantages in terms of CO2 emissions. The process based on coal gasification and nuclear cogeneration, capable of reducing emissions by up to 75% and saving up to 40% of coal consumption. While the process based only on CO2 and nuclear hydrogen cogeneration (without coal gasification), teoretically can operate witout any CO2 emission at all. Even this process can captured and utilize CO2 emissions from coal fired plant, and use it as a raw material for the process.